Perfect timing: sensitive periods for Montessori education and long-term wellbeing - Lillard, Angeline S.; Jiang, Richard Hua; Tong, Xin (Frontiers in Developmental Psychology, 2025)
Montessori is the most common alternative education in the world by far, and it exists both in public and private schools and extends from birth to university. A prior study found that Montessori attendance as a child, controlling for demographic factors including SES, was associated with higher adult wellbeing, and that the longer one had attended Montessori school, the higher one's adult wellbeing. Because few people remain in Montessori programs for all their precollege years, here we ask if there are more optimal ages, in terms of an association with long-term wellbeing, to attend Montessori schools (sensitive periods), and more optimal ages to transition from Montessori to conventional schools (sensitive transition points). Using factor scores derived from the responses of N = 1,907 adults (Mage 37, range 18–81 years) on standard measures of wellbeing, we analyzed whether adult wellbeing was higher if one had attended Montessori during specific age spans (3 to 6, 6 to 9, etc.). Although attending Montessori during every period through age 12 predicted higher adult wellbeing (compared to attending conventional schools), the strongest effects were found for attending Montessori rather than conventional programs during preschool (ages 3 to 6), and for attending it for 3 rather than just 2 preschool years. We next examined for optimal points of transition from Montessori to conventional schools, focusing especially on whether one transitioned at the end of one of Montessori's 3-year classroom cycles (ages 6, 9, and 12) or in the middle of those cycles (ages 4, 5, 7, 8, 10, and 11). Controlling for basic demographic variables, the wellbeing factor of Engagement was higher if one had transitioned out of Montessori at the end of one of the 3-year-cycles than if one transitioned in the middle of those cycles, and there was a trend for having higher General Wellbeing. We discuss the implications for parents and for education policy.